Words are powerful but LGBTQ2 equality requires more than a Trudeau apology - Gobbo, Daniel Del; Cossman, Brenda (The Globe and Mail, 2017)
For the government’s statement Tuesday to have substance, it needs to be accompanied by meaningful reforms that continue to improve the lives of lesbian, gay, bisexual and transgender Canadians everywhere
Keywords: Daniel Del Gobbo